Avaliação por RMN de alta resolução da presença de cereais não maltados na produção de cervejas - Esteves, Rafael Rodrigues (Universidade Federal de São Carlos, 2020)
Statistics show that beer is the most widely consumed alcoholic beverage in the world and it is made up of water, barley malt, hops and yeast as main ingredients. The use of non-malted cereals in beer production is common to reduce the production cost, however the amount used is not declared in the labels. Typically in industrial production, barley malt substitutes are the cheaper sub products from corn (Zea mays) and rice (Oryza sativa). To know about the capability of NMR on detection of different non-malted cereals in beer production, nine beers were produced with different percentages of barley malt, corn grains and rice flakes. The samples were collected during all important stages of production and fermentation. The method was developed with easily preparation of samples, just being a dilution of the sample in deuterated water to avoid errors associated with this step. The ¹H RMN spectra were acquired in a 9.4 Tesla (400 MHz) Bruker® equipment, model AVANCE III, using a 5 mm BBI probe, with the pulse sequence NOESYGPPR1D, being acquired and processed in the Topspin 3.5 pl.7 software. For the chemometric analysis (PCA) was used the AMIX® software version of the 3.9.3 package. Using PCA in the ¹H NMR spectra, it was possible to discriminate the groups of beers produced exclusively with barley malt from beers produced with 30% and 45% non-malted cereals. This analysis showed that the main compounds and metabolites responsible for this discrimination were succinic acid, α(1,4)-glucose, pyruvic acid, and alanine. Finally, it is possible to conclude that the use of ¹H NMR spectroscopy combined with chemometric analyzes were able to discriminate with high precision the presence of non-malted cereals in beer production. These results demonstrate the separation of groups of beers produced with different amounts of adjuncts. Although the results are still initial, they demonstrate the technique's potential for continuing this study and other work that uses NMR applied to food and beverages.
Study of the impact of using no malted cereals on beer production accompanied by high resolution NMR
Keywords: RMN; Cerveja; Cereais; NMR; Beer; CIENCIAS EXATAS E DA TERRA::QUIMICA